INOVASI PEMBELAJARAN PAI BERBASIS ONLINE DENGAN MODEL ASSURE - Palahudin Palahudin; Uus Ruswandi (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2021)
Abstrak: pada masa pandemic covid-19 pembelajaran PAI perlu mengadakan inovasi dan kreativitas yang baik untuk menjadikan pembelajaran yang asik dan menyenangkan. Tentunya tujuan yang diharapkan dari kompetensi dasarpun terpenuhi secara baik. Pendidik dituntut untuk mampu mengoperasikan teknologi secara baik dan kreatif agar terciptanya pembelajaran online aktif, komunikatif dan kreatif. Model ASSURE merupakan salah satu alternatif yang mampu meningkatkan hal tersebut. Penelitian ini merupakan kualitatif, dimana pembelajaran PAI materi wudhu dengan menggunakan model ASSURE. Selanjutnya hasil yang diperoleh akan dideskripsikan. Pelaksanaannya tetap mengikuti sintak model tersebut namun sedikit dimodifikasi sesuai pembelajaran online. Hasil yang diperoleh mengenai kemampuan berwudhu peserta didik dilihat dari niat wudhu naik 16%, tata cara wudhu naik 4%, bacaan wudhu naik 3% dan melafalkan do’a setelah wudhu naik 9%.Kata kunci: covid-19, model ASSURE, Pendidikan Agama IslamAbstract: During the Covid-19 pandemic, PAI learning needs to carry out good innovation and creativity to make learning fun and enjoyable. Of course, the objectives expected from basic competencies are fulfilled properly. Educators are required to be able to operate technology well and creatively in order to create active, communicative and creative online learning. The ASSURE model is an alternative that can improve this. This research is a qualitative study, where the learning of Islamic teaching on ablution material using the ASSURE model. Furthermore, the results obtained will be described. The implementation still follows the syntax of the model but is slightly modified according to online learning. The results obtained regarding the ability of students to perform ablution were seen from the intention of ablution to increase by 16%, the procedures for ablution increased by 4%, the reading of ablution increased by 3% and reciting prayers after wudu increased by 9%.Keywords: Covid-19, the ASSURE model, Islamic Religious Education